PENGUATAN MUTU PENDIDIKAN BERBASIS POTENSI KEARIFAN LOKAL DAERAH DESA TOYOMARTO KECAMATAN SINGOSARI KABUPATEN MALANG - Hardinata, Vanda; Dewi, Putri Kumala; Budiana, Nia (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2021)
Toyomarto Village, Singosari District, Malang Regency, has various economically valuable regional potentials and tourism potentials that can be developed. In the education sector, which is located in a remote area with multiple potentials such as Toyomarto Village, there has been insufficient attention from the local government in efforts to develop human resource activities. The lack of IT facilities in the education sector, especially in schools located in villages, has resulted in weak IT development in the era of the 4.0 industrial revolution. The selection of this theme for strengthening educational quality is expected to enhance human resources, particularly educators and students. The strengthening of educational quality based on local wisdom, especially in Toyomarto Village, aims to improve educational quality, particularly the quality of learning, by utilizing the existing potential in Toyomarto Village. Therefore, the community service team plans to implement a concept for strengthening educational quality in Toyomarto Village, Singosari District, Malang Regency, by conducting workshops/training on educational quality improvement based on local potential that can be maximized for educational enhancement. Furthermore, this collaborative planning for educational quality improvement is expected to have a positive impact on enhancing strategies, planning, media, and evaluation of learning in the Indonesian Language and Literature Education Program.